Attitude, Motivation and Barriers for CSR Engagement among Travel and Tour Operators in Nepal - Baniya, Rojan; Rajak, Kripa (Journal of Tourism and Hospitality Education, 2020)
The surging interest of tourists in responsible business practices and their global popularity is making CSR imperative for tourism SMEs, including TTOs of Nepal. Consequently, there has been a rise in CSR engagements among tourism SMEs in developing countries. Nonetheless, due to limited attention by researchers, knowledge about their CSR engagement is scant. The same is also true for TTOs residing in Nepal. In such a scenario, it is prudent to generate an understanding of CSR engagement of Nepali TTOs. For this reason, this exploratory study investigated various dynamics of CSR engagement among TTOs (n=141) registered in the National Association of Tour and Travel Agents through a paper-based survey. The results showed that half of TTOs claimed that they had incorporated CSR in their mission and strategy; they exhibited positive attitudes about the benefits of CSR to businesses, customers’ favorability towards businesses simple menting CSR, and the need for a higher value to CSR within the tourism industry. Societal benefits and wellbeing, and the opportunity to market their image among customers motivated them to engage in CSR, whereas lack of resources and knowledge restrained them. Three fourth of them claimed to practice CSR of some sort, and most of them intended to continue their CSR engagement in the future. Collectively, TTOs had a positive outlook towards CSR. However, there are some deterrents for them to engage in CSR. This study provides valuable baseline insights to formulate the right plans and policies to influence CSR employment by TTOs, ultimately leading to sustainable tourism.